O papel da luz no desenvolvimento de cenários para cinema de animação. Aplicação numa curta metragem. - Moreira, Ana Alícia da Silva (2018)
This research project aim to study the role of light in the construction of an environment and development of scenarios for digital animation, culminating in the directing of a short animation film. The plot is an adaptation of a fantastic tale called The Shaft, by the writer Nancy Kilpatrick. The story focuses on the obsession and fears of the main character and the mechanisms to avoid and resolve them. This study is approached in historical terms - analyzing practical cases of the role of light, and studying its roots in theater, film, photography and how the light is set and created, keeping in mind the specificities of an hybrid digital animation. In this short film strategies of the usage of light, in order to increase different narrative moments in the film, were applied.